PERSEPSI IBU HAMIL TERHADAP PENULARAN HIV KE BAYI DI WILAYAH KERJA PUSKESMAS PERAWANG KABUPATEN SIAK - Silvia Anita Yuningsih; Eti Afriyanti (Institut Kesehatan dan Teknologi Al Insyirah, 2020)
ABSTRACT HIV/AIDS case in Indonesia occupied the 5th position from Asian countries, based on statistical data of HIV prevalence in pregnancy mother is projected to increase from 0,38 % (2012) to 0,49 % (2016) and the number of pregnancy mother get positive HIV who need PPIA services will be increase from 13.189 in 2012 to 16.191 in 2016. The purpose of this study was to find the relationship between age, education, occupation and knowledge with the perception of pregnant women on HIV transmission to infants in Perawang Village. This research is quantitative with analytic design cross sectional approach. Samples in this study of 78 respondets accidental sampling. Data analysis univariate and bivariate. Based on statistic test showed that there were relationship between age, education, and knowledge with perception of pregnancy mother against transmission of HIV to infants in sub district Perawang, Perawang Community Health Center, Siak with p value < α 0,05. (Age <0.014, Education <0.018, and Knowledge <0.026). The results of this study also serve as information for pregnant women to cope with HIV transmission from mother to baby and is expected for health workers to further improve the provision of information by disseminating around HIV / AIDS material. Keywords : Age, education, occupation, knowlodge, HIV/AIDS